SISTEM INFORMASI INVENTORY BERBASIS WEB PADA PT. TELEKOMUNIKASI INDONESIA WITEL BANDUNG BARAT - Putri Utami; Prayoga Prayoga; Bramanto Fajri Prakoso (Universitas Widyatama, 2019)
PT. Telkom Witel West Bandung is the only state-owned company in the telecommunications and network sector in Indonesia, where SOEs can continue to develop to realize quality services and networks. Use it using information technology today. Inventory data processing at PT. West Witel Telkom is not well integrated, it is difficult to find data, including redundation of data and the length of time the report is made. The methodology currently in this inventory information system is Prototype, i.e. While the data uses observation and interview data. The method of development uses a structured method. The programming language is PHP and MySQL database. Information inventory system can display material data, receipt data, expenditure data, retrieval data and transaction data. With the implementation of this inventory information system, it is expected to facilitate PT. Telkom Witel West Bandung is related to the application of information inventory systems (speeding up data search, minimizing data redundancy and speeding up report generation), can achieve maximum results and can support information quickly and accurately.